Case report: Whole-exome sequencing identifies a novel DES mutation (p. E434K) in a Chinese family with cardiomyopathy and sudden cardiac death - Liu, Yu-Xing; Yu, Rong; Sheng, Yue; Fan, Liang-Liang; Deng, Yao (Frontiers in Cardiovascular Medicine, 2022)
Background Desmin is an intermediate filament protein that plays a critical role in the stabilization of the sarcomeres and cell contacts in the cardiac intercalated disk. Mutated DES gene can cause hereditary cardiomyopathy with heterogeneous phenotypes, while the underlying molecular mechanisms requires further investigation. Methods We described a Chinese family present with cardiomyopathy and sudden cardiac death (SCD). Whole-exome sequencing (WES) and bioinformatics strategies were employed to explore the genetic entity of this family. Results An unknown heterozygote missense variant (c.1300G > A; p. E434K) of DES gene was identified. The mutation cosegregates in this family. The mutation was predicted as pathogenic and was absent in our 200 healthy controls. Conclusion We identified a novel DES mutation (p. E434K) in a Chinese family with cardiomyopathy and SCD. Our study not only provided a new case for the study of the relationship between DES mutations and hereditary cardiomyopathy but also broadened the spectrum of DES mutations.